MEMBINA KELUARGA MUSLIM DI ERA GLOBAL: Pergumulan antara Tradisi dan Modernitas - Suharto, Toto (Sunan Kalijaga State Islamic University & The Asia Foundation, 2011)
This article talks about the patterns of Muslims in raising families with respect to the modern era. The Muslim family often faces forms of identity crises, faced in the global era with the need to hold on to tradition, while at the same time conforming to modernity. The best way to face such a conflict would be to engage in dialogue traditions and modernity. In that context, it needs to be pointed out that Islam does not always give the answers hoped for by its believers with respect to socio-cultural realities. This fact is related to the transcendent nature of Islam, in the form of normative-dogmatic requirements. This ground has led to theological conflicts between the need to hold on to normative doctrine and the desire to give new perpectives towards the doctrine as to be interpreted historically. This conflict has often sparked theological, intellectual and social conflicts within Muslims as a whole. Therefore, the Islamic conception that aims to establish an economically independent, traditionally rich and emotionally sensitive family, needs to be discussed, so that Muslim families can continue to survive in the midst of the global realities.